ПОДГОТОВКА IT СПЕЦИАЛИСТОВ УО БГУИР В ОБЛАСТИ 1С (International Journal of Innovative Technologies in Economy, 2018)
In conditions of a prompt computerization an integral part of vocational training as are new computer technologies. Occurrence and progress of packages of applied programs create huge possibilities for their use in the accounting and administrative account. Skill to make good use of new information technologies by preparation of experts – one of the major requirements shown to teachers of modern high school.Studying of a rate « the Accounting and administrative account » as well as, programming in 1С play a major part during vocational training the qualified experts and it is directed on formation of skill to analyze existing system of an information exchange at the enterprise for acceptance of administrative decisions in the organization and skills of practical construction of system of the administrative account at the enterprises of various patterns of ownership.